Green-synthesized iron oxide nanoparticles alleviates copper toxicity and enhance the morpho-physiological growth and tuber quality of potato (Solanum tuberosum L.) grown in contaminated soil - Hongyang Wang; Youhong Feng; Yan Yang; Rui Shi; Jiali Geng; Yunxin Kong; Muzammal Rehman; Zahid Maqbool; Shah Saud; Shah Fahad; Gang Deng (Journal of Agriculture and Food Research, 2025)
A pot study was carried out to explore the effectiveness of varying levels (0, 3, 6, 9, and 12 mM) of green-synthesized iron oxide nanoparticles (FeO-NPs) on morpho-physiological growth and tuber quality of Potato (Solanum Tuberosum L.) grown in copper (Cu) contaminated soils (S1 and S2). Results revealed that Cu contamination badly influenced the growth parameters of potato plants, but use of FeO-NPs at 9 mM significantly enhanced the morpho-physiological growth, antioxidant enzyme activities and tuber quality attributes in Cu contaminated soils. Among various treatments, highest increase in plant height, stem diameter, chlorophyll contents, fresh and dry biomass of potato were recorded in S1NP3 followed by S2NP3 as compared to control. Although highest malondialdehyde (MDA) contents were observed in S2NP0 (37.70 ± 1.14 nmol g−1) followed by S1NP0 (24.16 ± 1.64 nmol g−1) but FeO-NPs effectively reduced MDA content in S2NP3. Moreover, the activities of superoxide dismutase (SOD) and catalase (CAT) were significantly enhanced by 167.4 % and 308.6 %, and 169.2 % and 168.3 % respectively, in the S2NP3 treatment at the budding and flowering stages. Furthermore, maximum reduction in Cu content in the soil (46.9 %), shoots (56.8 %), leaves (84.1 %) and tubers (86.9 %) was also observed in S2NP3. Overall, green-synthesized FeO-NPs improved the growth, antioxidant activity, and quality of potatoes in Cu contaminated soils.